Peripheral Intravenous Catheter Placement Is an Underrecognized Source of Staphylococcus aureus Bloodstream Infection - Austin, Eloise D. (Open Forum Infect Dis, 2016)
Few studies have focused on the risks of peripheral intravenous catheters (PIVs) as sources for Staphylococcus aureus bacteremia (SAB), a life-threatening complication. We identified 34 PIV-related infections (7.6%) in a cohort of 445 patients with SAB. Peripheral intravenous catheter-related SAB was associated with significantly longer bacteremia duration and thrombophlebitis at old PIV sites rather than current PIVs.